2020
DOI: 10.1016/j.jhepr.2020.100113
|View full text |Cite
|
Sign up to set email alerts
|

Care of patients with liver disease during the COVID-19 pandemic: EASL-ESCMID position paper

Abstract: The coronavirus disease 2019 pandemic poses an enormous challenge to healthcare systems in affected communities. Older patients and those with pre-existing medical conditions have been identified as populations at risk of a severe disease course. It remains unclear at this point to what extent chronic liver diseases should be considered as risk factors, due to a shortage of appropriate studies. However, patients with advanced liver disease and those after liver transplantation represent vulnerable patient coh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
690
0
52

Year Published

2020
2020
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 434 publications
(750 citation statements)
references
References 45 publications
8
690
0
52
Order By: Relevance
“…48 Patients with NAFLD or steatohepatitis (NASH) usually have diabetes, hypertension and obesity, all of them associated with a severe course of COVID-19. 49 Cai et al analysed 14 patients infected with SARS-CoV-2 and preexisting NAFLD, 6 of which had severe disease and worse outcomes. 7 Ji and colleagues showed that patients with NAFLD had a higher risk of progression to severe COVID-19 and longer viral shedding time.…”
Section: Covid -19 and Cldmentioning
confidence: 99%
See 2 more Smart Citations
“…48 Patients with NAFLD or steatohepatitis (NASH) usually have diabetes, hypertension and obesity, all of them associated with a severe course of COVID-19. 49 Cai et al analysed 14 patients infected with SARS-CoV-2 and preexisting NAFLD, 6 of which had severe disease and worse outcomes. 7 Ji and colleagues showed that patients with NAFLD had a higher risk of progression to severe COVID-19 and longer viral shedding time.…”
Section: Covid -19 and Cldmentioning
confidence: 99%
“…EASL-ESCMID currently advises against reducing immunosuppressive therapy in patients with autoimmune liver disease and recommends that reductions should only be considered in case of severe COVID-19 under special circumstances (eg drug-induced lymphopenia or bacterial/fungal superinfection). 49 The World…”
Section: Yesmentioning
confidence: 99%
See 1 more Smart Citation
“…All these sequence and structural modelling evidences strongly support the concept that the SARS-CoV-2 RdRp is much more similar to the one from HCV than the one from negative-sense Influenza and Ebola RNA viruses. Therefore, repositioning of Sofosbuvir (Sovaldi®; Epclusa® by Gilead), the inhibitor of the HCV NS5B RdRp protein, as antiviral in the treatment of the SARS-CoV-2 infection has an extremely high potentiality of success, as recently postulated by others [17], and is suggested as a potential drug for the treatment of COVID-19 in the very recent EASL-ESCMID position paper [18]. This is further supported by the great diversity between the molecular structure of the Sofosbuvir and the inhibitors of Influenza and Ebola viruses currently evaluated in clinical trials (Fig.…”
mentioning
confidence: 98%
“…As COVID-19 the disease caused by SARS-CoV-2 continues to have a profound impact on global health, there have been a number of guidelines recently published addressing the management of patients with liver disease during the COVID-19 pandemic including the recently published EASL-ESCMID Position Paper, guidelines issued by the International Liver Cancer Association and the American Association for the Study of Liver Diseases (1)(2)(3). All publications present a sound discussion regarding the challenges face by both patients and clinicians alike in the management of chronic liver disease in the setting of this ongoing pandemic.…”
mentioning
confidence: 99%